In Utero Programming of Later Adiposity: The Role of Fetal Growth Restriction - Ousseynou Sarr; Kaiping Yang; Timothy R. H. Regnault (Journal of Pregnancy)
Intrauterine growth restriction (IUGR) is strongly associated with obesity in adult life. The mechanisms contributing to the onset of IUGR-associated adult obesity have been studied in animal models and humans, where changes in fetal adipose tissue development, hormone levels and epigenome have been identified as principal areas of alteration leading to later life obesity. Following an adverse in utero development, IUGR fetuses display increased lipogenic and adipogenic capacity in adipocytes, hypoleptinemia, altered glucocorticoid signalling, and chromatin remodelling, which subsequently all contribute to an increased later life obesity risk. Data suggest that many of these changes result from an enhanced activity of the adipose master transcription factor regulator, peroxisome proliferator-activated receptor-γ (PPARγ) and its coregulators, increased lipogenic fatty acid synthase (FAS) expression and activity, and upregulation of glycolysis in fetal adipose tissue. Increased expression of fetal hypothalamic neuropeptide Y (NPY), altered hypothalamic leptin receptor expression and partitioning, reduced adipose noradrenergic sympathetic innervations, enhanced adipose glucocorticoid action, and modifications in methylation status in the promoter of hepatic and adipose adipogenic and lipogenic genes in the fetus also contribute to obesity following IUGR. Therefore, interventions that inhibit these fetal developmental changes will be beneficial for modulation of adult body fat accumulation.